2023
DOI: 10.2147/ndt.s404176
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Aggressive Behavior and Impulsive and Aggressive Personality Traits in Stable Patients with Schizophrenia

Abstract: To explore the correlation between aggressive behavior and impulsive and aggressive personality traits in inpatients with schizophrenia. Methods: In total, 367 inpatients with schizophrenia were divided into two groups: the aggressive group and the non-aggressive group. We assessed inpatients' psychotic symptoms as well as their aggressive and impulsive personality traits using the Positive and Negative Symptom Scale, the Barratt Impulsiveness Scale, and the Buss-Perry Aggression Questionnaire. Results: Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…The results of this study showed that aggressive behavior were positively correlated with positive symptoms and childhood traumas in patients with schizophrenia, corroborated by prior investigations [ 31 , 32 ]. Per the assessment, positive manifestations in patients with schizophrenia included delusions, muddled thinking, bizarre behavior, and cognitive inconsistencies, all of which greatly affect how they interpret reality, resulting in extreme frustration, varying mood swings, increased arousal levels, and challenges in controlling actions, ultimately leading to aggressive behavior [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study showed that aggressive behavior were positively correlated with positive symptoms and childhood traumas in patients with schizophrenia, corroborated by prior investigations [ 31 , 32 ]. Per the assessment, positive manifestations in patients with schizophrenia included delusions, muddled thinking, bizarre behavior, and cognitive inconsistencies, all of which greatly affect how they interpret reality, resulting in extreme frustration, varying mood swings, increased arousal levels, and challenges in controlling actions, ultimately leading to aggressive behavior [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Aggressive conduct observed in individuals diagnosed with SCZ entails the display of destructive behaviors, encompassing verbal and physical assaults toward others, vandalism, as well as self-inflicted harm. These manifestations are frequently prompted by psychotic symptoms and environmental influences ( 10 , 11 ). Among all types of mental disorders, the occurrence of aggressive behavior is most prevalent in patients with SCZ.…”
Section: Introductionmentioning
confidence: 99%